Strigolactone and karrikin signal perception: receptors, enzymes, or both? - Janssen, Bart J.; Snowden, Kimberley C. (Frontiers in Plant Science, 2012)
The signaling molecules strigolactone (SL) and karrikin are involved in seed germination, development of axillary meristems, senescence of leaves and interactions with arbuscular mycorrhizal fungi. The signal transduction pathways for both SLs and karrikins require the same F-box protein (MAX2) and closely related α/β hydrolase fold proteins (DAD2 and KAI2). The crystal structure of DAD2 has been solved revealing an α/β hydrolase fold protein with an internal cavity capable of accommodating SLs. DAD2 responds to the SL analog GR24 by changing conformation and binding to MAX2 in a GR24 concentration-dependent manner. DAD2 can also catalyse hydrolysis of GR24. Structure activity relationships of analogs indicate that the butenolide ring common to both SLs and karrikins is essential for biological activity, but the remainder of the molecules can be significantly modified without loss of activity. The combination of data from the study of DAD2, KAI2 and chemical analogs of SLs and karrikins suggests a model for binding that requires nucleophilic attack by the active site serine of the hydrolase at the carbonyl atom of the butenolide ring. A conformational change occurs in the hydrolase that results in interaction with the F-box protein MAX2. Downstream signal transduction is then likely to occur via SCF complex-mediated ubiquitination of target proteins and their subsequent degradation. The role of the catalytic activity of the hydrolase is unclear but it may be integral in binding as well as possibly allowing the signal to be cleared from the receptor. The α/β hydrolase fold family consists mostly of active enzymes, with a few notable exceptions. We suggest that the DAD2 and KAI2 represent an intermediate where some catalytic activity is retained at the same time as a receptor role has evolved.